PANCASILA DAN PERUBAHAN SOSIAL: PERSPEKTIF INDIVIDU DAN STRUKTUR DALAM DINAMIKA INTERAKSI SOSIAL - Prayitno, Ujianto Singgih (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
The background of this review is the fact that today’s society marginalize Pancasila as the values and nmoral insocial interaction. By using contemporary sociological perspectives that develops relationships between individual and structures the writer concludes that pancasila as the vision of social change, see the reciprocal relation between individual and structure. It has greatly affect the quality of social change in the society. The consequence of this view is that Pancasila materialized in values and morality embodied in individual and collective level. Therefore it has become our collective duty to contextualized and implement Pancasila in a variety of direction of life in national and state levels.